Maximum strength in squats determines jumping height in young female volleyball players - Augustsson, S. R. (The Open Sports Sciences Journal, 2013)
Few data exist on the relationship between maximum strength and power performance, such as jumping ability in low-level female volleyball players. The aim of the present study was to determine the relationship between maximum strength and jumping performance in young female non-elite volleyball players before and after an in-season resistancetraining protocol. A 26-week, in-season resistance-training program was carried out on ten female volleyball players, aged 19 (±2). The 1 RM squat test was used to evaluate the players` maximum strength in the lower extremities and a vertical jump (VJ) test was used to assess functional performance and power. There was a significant enhancement of 69% (p=0.005) for the squat test and 9% for the VJ test (p=0.008). A strong significant relationship was found between the VJ test and the 1 RM squat test (r=0.68, r2=0.47, p=0.0014) at the pre-test and post-test (r=0.88, r2=0.77, p=0.001). When comparing the coefficients of correlation (r=0.68 and r=0.88) between the squat tests and VJ tests, the difference that was noted was significant (p<0.001). A strong significant relationship was also noted between the 1RM squat and VJ test relative to body weight at pre-test (r=0.89, r2=0.79, p=0.001) and post-test (r=0.95, r2=0.90), p<0.001). This study demonstrates that maximum strength in squats is a major predictive factor for jumping height in young female volleyball players. Female volleyball players might therefore consider focusing on maximum strength training to improve their jumping performance.